Plan de negocios para la empresa Innovación en Redes y Telecomunicaciones IRTELC. CIA. LTDA., de la ciudad de Latacunga. - Muso Cela, Tania Janeth (2022)
The present work entitled Business plan for the company Innovation in Networks and Telecommunications IRTELC CIA LTDA., had as objectives, to theoretically base the business plan, technology, telecommunications, the internet and the fiber optic network from the point of view of various authors; carry out a market, technical, financial study and analysis of the competition to assess the current situation regarding coverage with prospects for expansion and develop a business plan based on the service offered, marketing and finance for the benefit of the company . The methodology used for the research had a qualitative and quantitative approach of an elementary descriptive type, the independent variable covers business plan issues and its dependent variable handles aspects of the fiber optic internet service, for the research a survey was conducted to 366 people from a population of 7831, who are the inhabitants of the Eloy Alfaro parish, the formulation of the survey was under the parameters of the Likert scale, the financial evaluation shows the feasibility since the net present value is $5758 and the rate Internal return is 36%, from the moment the company begins to provide its services to the unsatisfied potential demand, it can be specified that in 3 months the investment would begin to be recovered. In view of all these results, the present business plan is shown to be viable.